Conducting polymer functionalized graphene-based electrochemical sensors for sensing pollutants in water - Siti Nur Akmar, Mohd Yazid; Aina Adriana, Che Adnan; Illyas, Md Isa; Mohamad Idris, Saidin; Mohamad Syahrizal, Ahmad; Chin, Suk Fun (International Association of Physical Chemists, 2023)
Recent trends in electrochemical sensors based on conducting polymer functionalized graphene for the detection of pollutants in water are highlighted in this review. Graphene has been the subject of a lot of scientific research to be composited with conducting polymers. Researchers are interested in graphene and its variants because they have a lot of good qualities, like good electrical and mechanical properties and very high surface area. With this review, we intend to arouse interest in the important topic of graphene and conducting polymer nanocomposite that is making significant advances in electrochemical sensing, especially for sensing pollutants in water.